SUPPLIER PERFORMANCE CRITICAL SUCCESS FACTOR IN OIL AND GAS INDUSTRY IN KALIMANTAN, INDONESIA - Alamsjah, Firdaus; Dewi, Jayanti Cinde Laras (Journal of Business Strategy and Execution, 2012)
The current activity trend of the oil and gas upstream sector shows increasing trend in production and exploration. In order to accommodate this, the availability of Goods and Services is becoming crucial to be fulfilled. Supply Chain Management (SCM) department needs to ensure that supplier will deliver the right Goods/ Services on time, that’s why supplier management is needed. Moreover, to ensure the continuity of operations and to prevent the delayed of operations, SCM need to identify which one of the supplier development strategy, which consist of supplier inventive, communication, and competitive pressure that is best applied for Goods supplier and best applied for Services supplier. The purpose and importance of this study is to deliver an outcome that will be of knowledge and beneficial to the oil and gas industry in Indonesia to improve their vendor performance system or as a knowledge reference for this industry to know whether the most critical supplier development strategy to be implemented on materials/goods supplier is the same or not with the most critical supplier development strategy to be implemented on services supplier, so the company is able to choose a good vendor performance management strategy and approach to gain better supply chain activity for better operation. By using multiple linear regression method, this research delivers a conclusion that communication turns out to be the best critical supplier development strategy to be applied for Goods supplier and Services supplier.